2019
DOI: 10.1039/c8ta11475g
|View full text |Cite
|
Sign up to set email alerts
|

New understanding of crystal control and facet selectivity of titanium dioxide ruling photocatalytic performance

Abstract: TiO2 with arbitrarily tunable facets is directly grown onto the conductive substrate. H+ promotes the growth of the high energy {001} facet rather than F−.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
118
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 70 publications
(121 citation statements)
references
References 54 publications
3
118
0
Order By: Relevance
“…It was found that when HF concentration was increased, the thickness of TiO 2{001} particles was decreased, while the lateral size of particles increased (Figures 1(a)−1(c)). This result is in agreement with our recent report [19]. In addition, the platelet TiO 2{001} particles were transformed to a hierarchical sheet-like structure and tended to aggregate, forming stacked hierarchical particles when HF/Ti ratio was reached to 3 and 4, respectively (Figures 1(c) and 1(d)).…”
Section: Resultssupporting
confidence: 93%
“…It was found that when HF concentration was increased, the thickness of TiO 2{001} particles was decreased, while the lateral size of particles increased (Figures 1(a)−1(c)). This result is in agreement with our recent report [19]. In addition, the platelet TiO 2{001} particles were transformed to a hierarchical sheet-like structure and tended to aggregate, forming stacked hierarchical particles when HF/Ti ratio was reached to 3 and 4, respectively (Figures 1(c) and 1(d)).…”
Section: Resultssupporting
confidence: 93%
“…The recent understanding on the true factors controlling the formation of low-index facets of TiO 2 reported by Butburee et al [17] has enabled the comprehensive matching of low-index facets in this work. The facile hydrothermal synthesis using tetrabutyl titanate (TTBT) as a Ti 4 + source, ammonium hexafluorotitanate (AFT) as an F À source, and hydrochloric acid (HCl) as an H + source was employed to successfully grow TiO 2 crystal with controllable facets onto a fluorine-doped tin oxide (FTO) substrate.…”
Section: Resultsmentioning
confidence: 95%
“…The recent understanding on the true factors controlling the formation of low‐index facets of TiO 2 reported by Butburee et al . has enabled the comprehensive matching of low‐index facets in this work.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations